MODEL MANAJEMEN PESERTA DIDIK DI MADRASAH ALIYAH - Luthfi Yasykur; Ahmad Sayuti; Asep Sumarna; Mohamad Erihadiana (Balai Diklat Keagamaan Bandung, 2023)
This study seeks to describe the administration of students at MA Al-Muthohhar Purwakarta, beginning with the admission of new students and ending with their graduation. This study employs a qualitative approach and a case study design. Data collection techniques use observation, interviews, and documentation. The data analysis method employs Miles and Huberman's data reduction, data presentation, and conclusions theories. According to the findings, the Management of Students at MA Al-Muthohhar included 1) Student Analysis through the conducting of joint meetings; 2) Acceptance of new students, via PPDB; 3) Selection of new students based on multiple written and oral examinations; 4) Orientation, which introduces incoming students to the school; 5) Student placement, assigning 133 new students to three sections based on the entrance examination’s result; 6) Student development through extracurricular activities and counseling; 7) Reporting, including student attendance, study agendas, report cards, etc; 8) Graduation and alumni, by attaining exam results and memorizing at least thirtieth juz.Keyword: Management; Students; Madrasah